MODEL PEMANFAATAN HASIL HUTAN BUKAN KAYU (HHBK) BAGI MASYARAKAT DI ZONA TRADISIONAL TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Mansur Mansur; Amir Tjoneng; Saida Saida (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
The community's need for land is very basic and continues to increase. With the expanding population and socio-economic activity, the uses of land is not only for a place to live, but rather to strive in order to survive, especially for rural communities. The National Park is an area that has specific characteristics, that have been defined for the function as a buffer system to protection of life by maintaining the existence of the original ecosystem in the expanse ecoregions. Bantimurung Bulusaraung National Park (TNBabul) with all the potentials and characteristics running these function by fixed pay attention and accommodate the needs of the local community especially in terms of land use and utilization. The various conflicts that occur as a result of government policies on land today need to be taken seriously by all parties. To carry out the management and land use with the protection functions, required comprehensive management regulatory mechanism involving all stakeholders. This study aims to identify, analyze and formulate a pattern management and land use on the TNBabul ecosystem sustainability and community survival. Land utilization and management by the community at TNBabul is done adaptively, one of them is non-timber forest products (HHBK) harvesting as an socio-economic effort in order to survive.